Impact of admitting diagnosis on survival from in-hospital cardiac arrest. (14th October 2021) - Sawhney, R; Meyer, J C; Whitaker, A B; Morris, C H; Tsai-Nguyen, G J; Perez, A; Mora, A
Abstract: Background: In-hospital cardiac arrest (IHCA) has an incidence of approximately 200, 000 adults per year in the United States. Most events occur in patients without known heart disease. The majority of IHCA data is heterogenous from registries, pooled databases, and insurance claims. We sought to examine single-center data from our institution over a 5-year period. Purpose: Does the category of admitting diagnosis impact the outcome of IHCA? We hypothesized that patients with cardiac admitting diagnoses would have higher rates of survival to discharge and discharge home due to an increased amount of shockable (ventricular) rhythms. Methods: All IHCA events over 5 years were identified, and 1, 105 charts were examined. Charts with missing information were excluded. Admitting diagnoses were reviewed and categorized by organ system. If there were multiple categories, the most causative was chosen. If equally causative, the most severe was chosen. Charts were organized by survival and sorted by the organ system of the admitting diagnosis. Categories with <10 patients were excluded from analysis. The primary outcome was survival to discharge. Secondary outcomes were initial rhythm, immediate survival, and discharge disposition. Initial rhythms were classified as asystole, pulseless electrical activity (PEA), and ventricular (ventricular tachycardia and fibrillation). Results: Patients with a cardiac category of admitting diagnosis (Table 1) had the highest rate of IHCA (29.68%) while hematologic had the lowest (1.45%). Immediate survival and survival to discharge respectively were highest for transplant patients (85.71%, 32.14%) and lowest for vascular (37.5%, 12.5%). The initial rhythm was predominantly PEA across all groups. Patients with cardiac and pulmonary diagnoses had higher rates of ventricular rhythms than asystole, which was reversed in the other groups. Discharge disposition (Table 2) home was highest for transplant (55.56%), cancer (52%), and cardiac (49.35%). Cardiac patients were nearly as likely to be discharged to an inpatient facility (45.46%). Pulmonary and gastrointestinal patients were most likely to be discharged to a long-term acute care hospital (28.89% and 28.57%, respectively). Neurologic patients were all, and trauma patients were mostly, discharged to inpatient facilities. Conclusion(s): In keeping with established data, cardiac patients were most likely to suffer an IHCA and had more ventricular rhythms than the other groups. However, their initial rhythm was predominantly PEA, they had the third-highest survival to discharge, and were predominantly discharged home. Transplant and trauma patients surprisingly had the highest survival to discharge while gastrointestinal and infectious patients had the lowest. The data presented herein can serve as a guide for clinicians to better predict survival to discharge and disposition for their patients who suffer an IHCA. Funding Acknowledgement: Type of funding sources: None.